A Subgroup of Latently Mycobacterium tuberculosis Infected Individuals Is Characterized by Consistently Elevated IgA Responses to Several Mycobacterial Antigens. (10th August 2015) - Baumann, Ralf; Kaempfer, Susanne; Chegou, Novel N.; Oehlmann, Wulf; Spallek, Ralf; Loxton, André G.; van Helden, Paul D.; Black, Gillian F.; Singh, Mahavir; Walzl, Gerhard
Abstract : Elevated antibody responses to Mycobacterium tuberculosis antigens in individuals with latent infection (LTBI) have previously been linked to an increased risk for progression to active disease. Studies in the field focussed mainly on IgG antibodies. In the present study, IgA and/or IgG responses to the mycobacterial protein antigens AlaDH, NarL, 19 kDa, PstS3, and MPT83 were determined in a blinded fashion in sera from 53 LTBI controls, 14 healthy controls, and 42 active TB subjects. Among controls, we found that elevated IgA levels against all investigated antigens were not randomly distributed but concentrated on a subgroup of < 30 % —with particular high levels in a small subgroup of 5 % comprising one progressor to active TB. Based on a specificity of 100 %, anti-NarL IgA antibodies achieved with 78.6 % sensitivity the highest accuracy for the detection of active TB compared to healthy controls. In conclusion, the consistently elevated IgA levels in a subgroup of controls suggest higher mycobacterial load, a risk factor for progression to active TB, and together with high IgG levels may have prognostic potential and should be investigated in future large scale studies. The novel antigen NarL may also be promising for the antibody-based diagnosis of active TB cases.